Uncertainty matters for trade: Uncovering the heterogeneous effects - Ibrahim Nana; Rasmane Ouedraogo; Sampawende Jules Tapsoba (Fondation pour les études et recherches sur le développement international (FERDI), 2024)
Revamping African and the United States Economic Ties: A Quest for More Trade and Investment Policarpo Gomes Caomique, Fatimata Belem, Sampawende Jules Tapsoba The ongoing global trend is marked by increasing geopolitical fragmentation, leading to policy differences, longer supply chains, and heightened uncertainty. Recent events such as the war between Russia and Ukraine, conflicts in the Middle East, and trade disputes between the United States and China demonstrate this global uncertainty. The World Uncertainty Index has steadily increased since the 1990s and peaked in 2020 due to factors like US-China trade tensions, Brexit, and the coronavirus pandemic.
Keywords: 330; Africa; Trade; Export; International trade